Antioxidant activity and cytotoxic effect of cassia essential oil - Chen, Feng Jie (2023)
Cassia essential oil is an odorant natural product extracted from the bark of Cinnamomum cassia through steam distillation. It comprises of a complex mixture of heterogenous group of secondary metabolites at different concentration with less severe side effects and toxicities. In this study, Cassia essential oil originated from China was purchased from online platform. Thin layer chromatography was conducted to identify metabolites’ polarity, followed by the detection of major group of secondary metabolites through qualitative phytochemical analysis. The essential oil was further evaluated for DPPH radical scavenging activity and cytotoxicity using MTT assay on Vero and A549 cells. Cassia essential oil contain both polar and non-polar compounds supported by the well-separated spots in thin layer chromatography in a mixture of hexane and ethyl acetate at ratio 10:3. Based on phytochemical analysis, a positive result was obtained for phenols, terpenoids, alkaloids, tannins, and flavonoids respectively. Nevertheless, saponins, quinones and glycosides were not detected in the essential oil. Cassia essential oil showed higher DPPH radical scavenging activity with EC50 values of 0.87 ±0.110 mg/mL (w/v) and 0.10 ± 0.130% (v/v), respectively. In MTT assay, Cassia essential oil exerted cytotoxicity selectively against A549 cells with IC50 values of 24.92 ± 0.079 µg/mL (24 hours), 20.49 ± iii 0.202 µg/mL (48 hours) and 7.14 ± 0.112 µg/mL (72 hours). No cytotoxicity was observed on Vero cells as the IC50 values were above 500 µg/mL in all the incubation periods. Therefore, Cassia essential oil is potential as antioxidant and cytotoxic agents. Future studies in the identification on the specific bioactive components in Cassia essential oil is crucial to correlate with various pharmacological activities.